2022
DOI: 10.1152/jn.00113.2022
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl effects on respiratory neuron activity in the dorsolateral pons

Abstract: Opioids suppress breathing through actions in the brainstem, including respiratory-related areas of the dorsolateral pons, which contain multiple phenotypes of respiratory patterned neurons. The discharge identity of dorsolateral pontine neurons that are impacted by opioids is unknown. To address this, single neuronal units were recorded in the dorsolateral pons of arterially perfused in situ rat preparations that were perfused with an apneic concentration of the opioid agonist fentanyl, followed by the opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Neurons were further grouped by discharge pattern, recognizing that separation into many subgroups decreases statistical power while summation of different neuron types into one group may confound subtype-specific remifentanil effects. Neuron subtypes matched those described in similar studies (Krolo et al, 2005;Smith et al, 2007;Rybak et al, 2008;Segers et al, 2008;Zuperku et al, 2019;Saunders et al, 2022), and especially studies of functional connections between PRG and preBötC/BötC (Rybak et al, 2008;Segers et al, 2008;Zuperku et al, 2019) to allow for functional interpretation of the results.…”
Section: Neuron Classificationmentioning
confidence: 73%
“…Neurons were further grouped by discharge pattern, recognizing that separation into many subgroups decreases statistical power while summation of different neuron types into one group may confound subtype-specific remifentanil effects. Neuron subtypes matched those described in similar studies (Krolo et al, 2005;Smith et al, 2007;Rybak et al, 2008;Segers et al, 2008;Zuperku et al, 2019;Saunders et al, 2022), and especially studies of functional connections between PRG and preBötC/BötC (Rybak et al, 2008;Segers et al, 2008;Zuperku et al, 2019) to allow for functional interpretation of the results.…”
Section: Neuron Classificationmentioning
confidence: 73%
“…Inhibitory transmission in the medullary rhythm generator influences respiratory rate in the case of phasic inhibition or causes sustained apnea in the case of prolonged inhibition ( Baertsch et al, 2018 ; Cregg et al, 2017 ; Sherman et al, 2015 ). We have recently found that inspiratory dorsolateral pontine neurons are silenced by fentanyl, whereas expiratory neurons are not ( Saunders et al, 2022 ). An intriguing possibility is that opioid-insensitive pontine neurons, which have continued activity during opioid exposure, send prolonged input to inhibitory neurons in the ventrolateral medulla to promote apnea, perhaps using pathways overlapping those involved in apneas evoked by excitation of certain parts of the KF area ( Saunders and Levitt, 2020 ; Dutschmann and Dick, 2012 ; Dutschmann and Herbert, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl-associated deficits in respiratory patterning result from a reduced activity of pontine inspiratory neurons, while apnea is observed after the loss of all phasic pontine activity and sustained tonic expiratory neuron activity. Using in situ rat preparations of the arterially perfused dorsolateral pons, neurons were categorized based on their respiratory-associated discharge pattern after incubation with an apneic fentanyl concentration [ 16 ]. When exposed to fentanyl, the inspiratory neurons were silenced or exhibited a reduced firing frequency, while the expiratory neurons only reduced their tonic firing frequency.…”
Section: Neurorespiratory Effects Of Fentanyl and Analogsmentioning
confidence: 99%